Effects of a wearable device and functional wear on spinal alignment and jump performance - Hayato Ikeda; Takayuki Miyamori; Junji Katsuhira; Ryuichi Sawa; Yu Shimasaki; Yuji Takazawa; Masafumi Yoshimura (Elsevier, 2021)
Background/Objective: To elucidate the effects of walking exercise using a wearable device and functional wear on spinal alignment and jump performance. Methods: In total, 27 female college soccer players were randomly divided into two groups: trunk solution (TS) and compression garments (CGs). Spinal alignment, jump performance, and electromyography activity during the jump performance of the two groups were measured after a 20-min walking exercise. The values for each group were compared t pre- and post-intervention. Results: The flexibility of the lower thoracic vertebrae in spinal alignment was increased during extension in the TS group. However, the post-value of the abdominal external oblique muscle during a countermovement jump (CMJ) was significantly lower than its pre-value (p < 0.05). In addition, even though spinal alignment was not affected in the CG group, post-values of the jump height during squat jump and CMJ were significantly higher than their pre-values (p < 0.05). Furthermore, the post-value of the biceps femoris during the countermovement jump with arm was significantly lower than its pre-value (p < 0.05). Conclusion: Our study suggested that walking exercise using TS may increase the range of motion of the lower thoracic vertebrae in athletes and reduce the muscular activity of the vastus lateralis during CMJ. Additionally, although spinal aliment is not affected, the jump height may increase using CGs.